Sosialisasi Pembuatan Pestisida Nabati Daun Pepaya pada KWT Turi Makmur Kota Blitar - Ningrum, Anisa Sulistya; Adelia Regina Putri; Noor Rizkiyah; Gideon Setyo Budiwitjaksono (EDUPEDIA Publisher, 2023)
The majority of farmers in Indonesia use chemical pesticides in cultivating their crops. Residues of chemical pesticides when used continuously will be harmful to the surrounding environment. Botanical pesticides are an alternative to chemical pesticides made from natural ingredients, namely plants. One of the plants that can be used as a vegetable pesticide is papaya leaves. KWT Turi Makmur has not utilized papaya leaves as a vegetable pesticide. The socialization regarding the manufacture of papaya leaf vegetable pesticides aims to provide knowledge and utilize natural materials around to become vegetable pesticides. The method used is observation, practice of making papaya leaf vegetable pesticides, and implementation consisting of outreach, demonstrations, and handing over of plant pesticides. As a result, KWT Turi Makmur received new insights and was proactive in terms of using natural ingredients and how to make them into vegetable pesticides. The main raw materials of vegetable pesticides consist of papaya leaves, garlic and cayenne pepper while the supporting materials are dishwashing soap and water. It is important to carry out socialization and training activities in order to obtain maximum results in the prevention and control of plant pests, where previously chemical pesticides were used which had harmful risks to living things and the surrounding environment.